Stable QTLs for Plant Height on Chromosome A09 Identified From Two Mapping Populations in Peanut (Arachis hypogaea L.) - Lv, Jianwei; Liu, Nian; Guo, Jianbin; Xu, Zhijun; Li, Xinping; Li, Zhendong; Luo, Huaiyong; Ren, Xiaoping; Huang, Li; Zhou, Xiaojing; Chen, Yuning; Chen, Weigang; et al. (Frontiers in Plant Science, 2018)
The peanut (Arachis hypogaea L.) is an important grain legume extensively cultivated worldwide, supplying edible oil and protein for human consumption. As in many other crops, plant height is a crucial factor in determining peanut architecture traits and has a unique effect on resistance to lodging and efficiency of mechanized harvesting as well as yield. Currently, the genetic basis underlying plant height remains unclear in peanut, which have hampered marker-assisted selection in breeding. In this study, we conducted a quantitative trait locus (QTL) analysis for peanut plant height by using two recombinant inbred line (RIL) populations including “Yuanza 9102 × Xuzhou 68-4 (YX)” and “Xuhua 13 × Zhonghua 6 (XZ)”. In the YX population, thirty-eight QTLs including ten major QTLs from nine chromosomes were detected in four environments, and eight consensus QTLs integrated by meta-analysis expressed stably across multiple environments. In the XZ population, three major QTLs and seven minor QTLs from six chromosomes were detected across three environments. Generally, most major QTLs from the two populations were located on pseudomolecule chromosome 9 of Arachis duranesis (A09), indicating there would be key genes on A09 controlling plant height. Further analysis revealed that qPHA09.1a from the XZ population and one consensus QTL, cqPHA09.d from the YX population were co-localized in a reliable 3.4 Mb physical interval on A09, which harbored 161 genes including transcription factors and enzymes related to signaling transduction and cell wall formation. The major and stable QTLs identified in this study may be useful for further gene cloning and identification of molecular markers applicable for breeding.